Is Ethics Nonsense?: The Imagination, and the Spirit against the Limit - Chen, Melvin (2016)
This article examines three exegetical approaches to Wittgenstein: the positivist approach, the ineffability approach, and the resolute approach. After revealing the defects and inconsistencies of the first two exegetical approaches, it adopts the resolute approach and rejects the possibility that a limit may be drawn between garden-variety nonsense and important nonsense. It then proceeds to outline a Wittgensteinian approach to ethics that pertains to the imagination and the spirit. It concludes with an excursus into literary ethics—which is this writer’s main area of interest—and how it might plausibly square with the demands of a Wittgensteinian ethic.